2020
DOI: 10.1158/1078-0432.ccr-20-3901
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Lurbinectedin for the Treatment of Metastatic Small Cell Lung Cancer

Abstract: On June 15, 2020, the FDA granted accelerated approval to lurbinectedin for the treatment of adult patients with metastatic small cell lung cancer (SCLC) with disease progression on or after platinum-based chemotherapy. Approval was granted on the basis of the clinically meaningful effects on overall response rate (ORR) and duration of response (DOR), and the safety profile observed in a multicenter, open-label, multicohort clinical trial (PM1183-B-005-14, NCT02454972), referred to as Study B-005, in patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…Moreover, the lack of effective molecular therapies as well as the immune-evasive tumor microenvironment makes the treatment of MPM particularly challenging [ 5 , 6 , 7 , 8 , 9 , 10 , 42 ]. Because MPM currently lacks peculiar oncogenic drivers, we have explored the potential therapeutic efficacy of lurbinectedin, an alkylating agent which recently received FDA-conditional approval for the treatment of metastatic small cell lung cancer patients relapsing after chemotherapy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lack of effective molecular therapies as well as the immune-evasive tumor microenvironment makes the treatment of MPM particularly challenging [ 5 , 6 , 7 , 8 , 9 , 10 , 42 ]. Because MPM currently lacks peculiar oncogenic drivers, we have explored the potential therapeutic efficacy of lurbinectedin, an alkylating agent which recently received FDA-conditional approval for the treatment of metastatic small cell lung cancer patients relapsing after chemotherapy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lurbinectedin (PM01183) is a marine-derived anticancer drug that exerts a potent antitumor activity in different cancer cell lines and xenografts models and is currently under clinical evaluation in several tumor types [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Recently, the FDA has released a conditional approval for lurbinectedin for the treatment of second-line metastatic small cell lung cancer patients [ 36 ] while promising antitumor activity has been reported in MPM patients in second- and third-line [ 37 ]. However, there are no data available on the role of lurbinectedin as monotherapy or in combination in the first-line treatment of MPM.…”
Section: Introductionmentioning
confidence: 99%
“…In June 2020, the United States Food and Drug Administration (FDA) granted accelerated approval to lurbinectedin for adult patients with metastatic small cell lung cancer with disease progression on or after platinum-based chemotherapy. 5 Lurbinectedin plus doxorubicin showed synergistic antitumor effect in small cell lung cancer xenografted tumors. Improved activity with this combination and activity observed for lurbinectedin Original research in a study of humans 6 prompted a phase I trial to evaluate this combination in advanced solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SCLC is characterized by early and widespread metastatic dissemination and a remarkable response to chemotherapy that is almost invariably followed by the development of drug resistance 4 . The first-line therapy for patients with SCLC has not changed for several decades; however, studies have recently shown that lurbinectedin could be an effective second-line therapy 5 . Although it has been shown that SCLC has a high frequency of TP53 and RB1 mutations, these gene mutations are not effective drug targets 3 , 6 .…”
Section: Introductionmentioning
confidence: 99%